Positive Impact of Thermal Manipulation During Embryogenesis on Foie Gras Production in Mule Ducks - Massimino, William; Davail, Stéphane; Bernadet, Marie-Dominique; Pioche, Tracy; Tavernier, Annabelle; Ricaud, Karine; Gontier, Karine; Bonnefont, Cécile; Manse, Hélène; Morisson, Mireille; Fauconneau, Benoit; Collin, Anne; et al. (Frontiers in Physiology, 2019)
Animal studies have shown that very early life events may have programing effects on adult metabolism and health. In this study, we aim, for the first, time to elucidate the effects of embryonic thermal manipulation (TM) on the performance of overfed mule ducks, in particular for the production of foie gras (fatty liver). We designed three embryonic TMs with different protocols for increasing the incubation temperature during the second part of embryogenesis, to determine whether hepatic metabolism could be “programed” to improve its fattening response to overfeeding at the age of three months. Initial results confirm that an increase in the incubation temperature leads to faster development (observed for all treated groups compared to the control group), and a decrease in the body surface temperature at birth. Thereafter, in a very innovative way, we showed that the three TM conditions specifically increased liver weights, as well as liver lipid content after overfeeding compared to the non-TM control group. These results demonstrate that embryonic TM effectively “programs” the metabolic response to the challenge of force-feeding, resulting in increased hepatic steatosis. Finally, our goal of improving foie gras production has been achieved with three different embryonic thermal stimuli, demonstrating the high reproducibility of the method. However, this repeatability was also perceptible in the adverse effects observed on two groups treated with exactly the same cumulative temperature rise leading to a reduction in hatchability (75 and 76% vs. 82% in control), in addition to an increase in the melting rate after cooking. These results suggest that embryonic thermal programing could be an innovative and inexpensive technique for improving foie gras production, although the specific protocol (duration, level or period of temperature increase), remains to be elucidated in order to avoid adverse effects.